Pengaruh Pendidikan Kesehatan Metode Audio Visual terhadap Perilaku Pemeriksaan Inspeksi Visual Asam (IVA), pada Wanita Usia Subur Di Wilayah Puskesmas Bengkulu Tengah Tahun 2020 - Warman Alamsyah; Defriman Djafri; Khairul Andri (Universitas Batanghari Jambi, 2020)
Cervical cancer (cervical) becomes a health problem especially for women of childbearing age who have had sexual intercourse resulting in unnecessary things so that IVA examination is not optimal. the purpose of this study was to determine the effect of audivisual methods of health education on the behavior of the Visual Acid Inspection (IVA), in Fertile Women in the Public health center working area. The design of this study is the Quasy Experiment Pre-post With Control Group. The number of samples is 60 women of childbearing age (WUS) consisting of 30 women of childbearing age (WUS) intervention group and 30 women of childbearing age (WUS) control group. The technique in sampling uses total sampling. Data were analyzed using the Independent Samples T-test. The results showed that there was a significant influence on knowledge (p value = 0.006), attitudes (p value = 0,000) and inspection behavior (p value = 0.004). Conclusion This audiovisual method of health education is effective in improving the knowledge, attitudes and behavioral examination of Visual Acid Inspection (IVA), in Fertile Women. The audiovisual method of health education can be used by the Public health center as an innovation in conveying information, especially for PTM and Posbindu program managers